Monitoring Evaluation Analysis of Tourist Village Development: A Case of Kemiren, Banyuwangi - Poeti Nazura Gulfira Akbar; Annisa Marsya Safira (Ministry of Tourism and Creative Economy/Tourism and Creative Economy Agency Republic of Indonesia, 2023)
The Ministry of Tourism and Creative Economy has set a target to increase the number of tourist villages classified as advanced to self-sufficient. In order to accomplish this, the Ministry organized training sessions to help and support the locals in enhancing their capability to manage their village as a tourist destination. One of the tourist villages where the training was provided was Desa Kemiren in Banyuwangi. The village received assistance in the aspect of tour guiding as the current status of Desa Kemiren is a developed tourist village. To make sure that the training meets the demands of the local community, monitoring and assessment analysis is required. Taking into account the significance of tour guides in delivering tourism services, this study investigates the implementation of tour guide training in Desa Kemiren. The research aims to analyse the monitoring evaluation of tour guide training based on stakeholders' perspectives. The study uses a qualitative method, and the data collection was collected through semi-structured interviews with six respondents, comprised of representatives of the government, community, and Kemiren villagers. The result demonstrates that this training is an attempt by the government to make the village self-sufficient in terms of problem identification. According to the viewpoint of the community, they took part because they need help developing the village to become an advanced tourism town and become independent. It can be seen that the purpose of the three main stakeholders involved in this program is aligning with one another